The hues of twilight years A phenomenology on the sexuality of Filipino gay Men in later life. - Dulfo, Erika M.; Lopena, Jona Jane I.; Mayo, Ian Carlo D. (Tacloban City Erika M. Dulfo, 2013)
This study presents a phenomenology of old gay men vis-a-vis their perceived sexuality. A unique segment of the population, approximately 10% statistically, this group has yet to be researched in the Philippines and has received relatively little attention among research institutions. This deficiency in literature is particularly noteworthy considering the overall increase in heteronormative aging research. The purpose of the study herein is to take a closer look on the lives of gay men during their twilight years, to examine the interplay of sexuality, aging and gender, present their experiences firsthand, life stories, remarks and inner concepts. The study attempts to learn and understand the components of sexuality among gay men in old age, and whether or not aging brings a change in the understanding of homosexuality. Taking a subjective value, sexuality is established through three major perspectives; 1) biological, 2) sociological, and 3) psychological with an inclination on the last two viewpoints. Findings show that aging as gay men means living without contradictions. It was an interesting outcome that the common image of older gays as being depressed, lonely and despairing is empirical groundless. Being old gays, it turns out, has some redemptive aspects, including liberation from sexual influences, multiple social obligations, and reckless personal choices in life.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban
Keywords: Social Science